Overlapping euchromatin/heterochromatin- associated marks are enriched in imprinted gene regions and predict allele-specific modification - Wen, Bo; Wu, Hao; Bjornsson, Hans; Green, Roland D.; Irizarry, Rafael; Feinberg, Andrew P. (Genome Research, 2008)
Most genome-level analysis treats the two parental alleles equivalently, yet diploid genomes contain two parental genomes that are often epigenetically distinct. While single nucleotide polymorphisms (SNPs) can be used to distinguish these genomes, it would be useful to develop a generalized strategy for identifying candidate genes or regions showing allele-specific differences, independent of SNPs. We have explored this problem by looking for overlapping marks in the genome related to both euchromatin (histone H3 dimethyl lysine-4 [H3K4Me2]) and heterochromatin (DNA methylation [DNAm]). “Double hits” were defined by the intersection of H3K4Me2 and DNAm. For the top 5% of marks, defined by a sliding window, imprinted gene regions were enriched for double hits 5.4-fold. When the location information of CTCF binding sites were integrated, the “triple hits” were enriched 76-fold for known imprinted genes in the regions studied. The double hits in imprinted genes were found to occur usually at the site of alternative or antisense transcripts. In addition, four of four imprinted genes tested showing double hits also showed allele-specific methylation. We suggest that overlapping euchromatin/heterochromatin marks are common and are enriched for epigenetically distinct parental chromosome regions. Furthermore, we developed a novel approach to identifying allele-specific marks that is SNP independent, by fractionating using H3K4Me2 antibodies followed by DNA methylation analysis.